Three-dimensional kinematics analysis of blind football kicking - Sakuma, T.; Kobayashi, M.; Kinoshita, H.; Matsui, Y.; Kobayashi, Y.; Watanabe, M. (Sports Biomechanics, 2023)
The purpose of this study was to identify critical technical points that lead to increased ball speed in a maximal toe kick with no run-up (a "static kick") in blind football. Six visually impaired male players and eight sighted male players participated in the experiment. All participants wore a blindfold to fully remove visual information and performed the static kick. The motion was captured three-dimensionally using an optical motion analysis system. Our results demonstrated that ball speed, maximum linear velocity of the kicking-side thigh, and maximum angular velocity of the kicking-side shank for the sighted player group were significantly greater than those for the visually impaired player group. The sighted players tended to perform the static kick in a similar motion pattern, which was characterised by a backwards rotation of the torso to adequately extend the kicking-side hip joint during the back-swing phase and a stable posture of the lower torso on the frontal plane during the forward-swing phase. This motion pattern is critical to both acceleration of the kicking-side foot and orientation of the foot for a more precise ball contact position.